Сучасні аспекти формування інвестиційного клімату в аграрному секторі економіки - Зубков, Руслан Сергійович; Скупський, Руслан Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Визначено основні фактори, що впливають на інвестиційну привабливість аграрного сектору економіки. Проведено аналіз основних чинників, що впливають на інвестиційний клімат, зокрема політичних, економічних, соціальних, технологічних, інфраструктурних та екологічних аспектів. Визначено роль держави у формуванні сприятливих умов для залучення інвестицій, зокрема через удосконалення законодавчої бази та підтримку інноваційних рішень агропродовольчої сфері. Досліджено динаміку надходження капітальних та прямих іноземних інвестицій в аграрний сектор України в останній період. Обґрунтовано напрямки покращення інвестиційної привабливості аграрного сектору України, через удосконалення земельного законодавства, введення нових фінансових інструментів та адаптацію українського законодавства до європейських стандартів Для покращення інвестиційного клімату в агропродовольчій сфері необхідні комплексні заходи, включаючи реформування законодавства, державну підтримку, інвестування у новітні технології та розвиток інфраструктури. Лише за таких умов аграрний сектор зможе реалізувати свій інвестиційний потенціал і стати важливим драйвером економічного зростання країни. Успіх цих заходів залежить від спроможності влади, бізнесу та суспільства взаємодіяти для створення стабільних та сприятливих умов для інвестицій.

The attractiveness of investment in the agricultural sector is an important aspect of Ukraine's economic development, as it not only ensures food security but also has significant potential for growth and modernization. With its fertile land and favorable climatic conditions, Ukraine's agricultural economy can become a powerful engine for attracting foreign investment, which will help increase productivity and competitiveness. The purpose of the study is to comprehensively analyze the factors that affect the investment potential and attractiveness of Ukraine's agricultural sector and to identify ways to improve them in the face of current challenges, through the development of practical recommendations for improving the investment potential of agri-food production, etc. The main factors affecting the investment attractiveness of the agricultural sector of the economy are identified. An analysis of the main factors affecting the investment climate, including political, economic, social, technological, infrastructure, and environmental, is carried out. The state's role in creating favorable conditions for attracting investment is determined, particularly by improving the legislative framework and supporting innovative solutions in the agri-food sector. The dynamics of capital and foreign direct investment in the agricultural sector of Ukraine in the recent period are studied. The author substantiates how to improve the investment attractiveness of the agricultural sector of Ukraine by improving land legislation, introducing new financial instruments, and adapting Ukrainian legislation to European standards. Comprehensive measures, including legislative reform, government support, investment in the latest technologies, and infrastructure development, are needed to improve the investment climate in the agri-food sector. Only under these conditions will the agricultural sector realize its investment potential and become an important driver of economic growth. The success of these measures depends on the ability of the government, business, and society to interact to create stable and favorable conditions for investment.
Modern aspects of investment climate formation in the agricultural sector of the economy
Keywords: інвестиційна привабливість; аграрний сектор; агропродовольча сфера; інвестиційний потенціал; державна підтримка; прямі іноземні інвестиції; investment attractiveness; agricultural sector; agri-food sector; investment potential; state support; foreign direct investment